1932
DOI: 10.1128/jb.23.6.455-472.1932
|View full text |Cite
|
Sign up to set email alerts
|

Agglutination and Dissociation Studies with Lactobacilli

Abstract: Attempts to classify lactobacilli have been many and varied. Such different criteria of classification as morphology, acid production, carbohydrate fermentation, surface-tension resistance and serological reactions have been used only to result in a tangle of miscellaneous data which tend to increase rather than to clarify the discrepancies in the literature. It is not the purpose of this communication to furnish serological data which will solve the problem, but rather to bring out a few points which may expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1937
1937
1938
1938

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…R to S dissociation has not been accomplished. The dissociative path of this species of lactobacillus was directly opposite to that of L. acidophilus as shown by Upton and Kopeloff (1932) and Raney and Kopeloff (1934) who consistently failed to induce S to R variation but readily produced R to S transformation.…”
Section: Dissociationmentioning
confidence: 89%
“…R to S dissociation has not been accomplished. The dissociative path of this species of lactobacillus was directly opposite to that of L. acidophilus as shown by Upton and Kopeloff (1932) and Raney and Kopeloff (1934) who consistently failed to induce S to R variation but readily produced R to S transformation.…”
Section: Dissociationmentioning
confidence: 89%
“…Since so few strains were used our results should be considered suggestive rather than conclusive. However it is tempting to correlate them with the findings of Upton and Kopeloff (1932) who used the same strains. They showed that the rough form appeared to be antigenically distinct from the smooth form in both L. acidophilus and L. bulgaricus.…”
Section: Niumbeir Lactmlcillfusmentioning
confidence: 99%